HUBUNGAN PENGETAHUAN DENGAN PERILAKU PERSONAL HYGIENE PADA ANAK DI PANTI REHABILITASI YANG BERHADAPAN DENGAN HUKUM - Novita*, Regina Vidya Trias (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2024)
Personal hygiene behavior is behavior that is carried out by someone to maintain personal hygiene to avoid diseases, especially skin diseases. This behavior cannot be separated from the knowledge that an individual has to help carry it out. This study aims to determine the relationship between knowledge and personal hygienic behavior in children at the Rehabilitation Center for Children in Conflict with the Law. A cross-sectional approach was used for this study, with a total of 60 participants. The results showed that respondents had good knowledge of personal hygiene, namely 29 people (48.3%), and good personal hygiene behavior, namely 29 people (48.3%). The Chi-square bivariate analysis showed a p-value of 0.360, more than the value of 0.05, which means that Ha is denied, so it can be concluded that there is no significant relationship between knowledge and personal hygiene behavior in children in rehabilitation institutions. The orphanages need to carry out strict monitoring and also support the fostered children regarding the importance of maintaining and caring for personal hygiene to avoid skin diseases so that it can generate motivation and enthusiasm for them to continue to routinely maintain personal hygiene.